2000
DOI: 10.1103/physrevb.62.14736
|View full text |Cite
|
Sign up to set email alerts
|

Pretransitional diffuse neutron scattering in the mixed perovskite relaxorK1xLix

Abstract: Several previous studies of K 1Ϫx Li x TaO 3 ͑KLT͒ have revealed the presence, above the structural transition, of polar nanoregions. Recently, these have been shown to play an essential role in the relaxor behavior of KLT. In order to characterize these regions, we have performed a neutron-scattering study of KLT crystals with different lithium concentrations, both above and below the critical concentration. This study reveals the existence of diffuse scattering that appears upon formation of these regions. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
21
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 23 publications
(30 reference statements)
9
21
1
Order By: Relevance
“…The temperature interval ⌬T of the pretransitional region is determined to be 40 K in both KTL-3 and KTL-7, which agrees with the result of the neutron diffuse scatterings in KLT-6. 7 The possible picture of the pretransitional region is as follows: In the cubic phase, dipole moments produced by off-centered Li ions align along one of the symmetry equivalent ͗100͘ directions. Below T B , individual Li dipoles start to associate to form PNRs as a result of intracorrelations of Li dipoles.…”
Section: A Pretransitional Region Between T P and T Bmentioning
confidence: 99%
See 1 more Smart Citation
“…The temperature interval ⌬T of the pretransitional region is determined to be 40 K in both KTL-3 and KTL-7, which agrees with the result of the neutron diffuse scatterings in KLT-6. 7 The possible picture of the pretransitional region is as follows: In the cubic phase, dipole moments produced by off-centered Li ions align along one of the symmetry equivalent ͗100͘ directions. Below T B , individual Li dipoles start to associate to form PNRs as a result of intracorrelations of Li dipoles.…”
Section: A Pretransitional Region Between T P and T Bmentioning
confidence: 99%
“…5 On the other hand, Toulouse et al pointed out that KLT is a kind of relaxor based on dielectric dispersion characteristics 6 and neutron diffuse scattering experiments. 7 Recent observations using an optical second-harmonic generation ͑SHG͒ microscope also support the relaxor nature of KLT-3 because of the marked history dependence of SHG intensities 8 which is similar to that of a prototype relaxor Pb͑Mg 1/3 Nb 2/3 ͒O 3 ͑PMN͒. 9,10 To be a real relaxor, the following criteria should be satisfied: ͑1͒ the characteristic frequency dispersion obeys the Vogel-Fulcher ͑VF͒ law and ͑2͒ polar nanoregions ͑PNRs͒ appear in a temperature range above T m .…”
Section: Introductionmentioning
confidence: 99%
“…This study follows a similar study of another mixed perovskite relaxor, K 1Ϫx Li x TaO 3 ͑KLT͒, which provided the correlation length or size of the polar nanoregions as a function of temperature. 13 In contrast to KLT, PZN exhibits not only substitutional chemical disorder but also charge disorder. Moreover, due to lone electron pair effects, Pb 2ϩ ions form partially covalent bonds with the neighboring oxygen atoms, which results in the off-centering of lead and in an additional local electric dipole moment.…”
mentioning
confidence: 99%
“…[17][18][19][20][21][22] Much attention has also been directed to determining the correlation length of the Li-induced dipoles through various experiments, such as Raman scattering, 23 dielectric measurement, 24 second-harmonic generation, 25,26 x-ray diffuse scattering, 27 and neutron diffuse scattering. 28 The reported correlation lengths are summarized in Table II in the study by Yong et al 28 Azzini et al have also proposed the presence of two kinds of correlation: dipolar and quadrupolar. 25 Raman scattering 29 and x-ray scattering 27 studies have revealed that the structural change takes place in KLT from cubic to tetragonal at the dipole freezing temperature.…”
Section: Introductionmentioning
confidence: 93%